A Synthetic Route for the Preparation of Core-Shell Nanoparticles Using a Protective Carbon Layer and Ozone Treatment. Issue 5 (1st January 2018) - Cho, Youngick; Lee, Hojin; Jeong, Yoonjae; Kim, Hansung
Abstract : A novel synthetic process was developed to synthesize nano-sized core-shell catalysts through atomic rearrangement by heat-treatment. Agglomeration of nanoparticles caused by the high-temperature heat-treatment was alleviated by using a modified protective coating method. In this method, the carbon layer formed by the carbonization of polydopamine serves as a protective coating layer, which suppresses the sintering of the catalyst particles continuously until the high-temperature heat-treatment is completed. Later, the carbonized carbon layer is removed by ozone treatment because it blocks the active site of the catalyst. Since ozone is a highly oxidative gas, it can selectively remove the carbon layer at room temperature in just 7 minutes without affecting the physical properties of the catalyst itself, which makes this method suitable for mass production. The Pt-based alloy catalyst was prepared by this unique process was proved to have a Pt-rich shell structure, and the particles can remain small (∼5 nm) even after high-temperature heat-treatment, thus exhibiting high oxygen reduction reaction (ORR) activity in fuel cells.